Stroke: working toward a prioritized world agenda. - Hachinski, V; Donnan, G; Gorelick, P; Hacke, W; Cramer, S; Kaste, M; Fisher, M; Brainin, M; Buchan, A; Lo, E; Skolnick, B; Furie, K; et al. (2010)
BACKGROUND AND PURPOSE: The aim of the Synergium was to devise and prioritize new ways of accelerating progress in reducing the risks, effects, and consequences of stroke. METHODS: Preliminary work was performed by 7 working groups of stroke leaders followed by a synergium (a forum for working synergistically together) with approximately 100 additional participants. The resulting draft document had further input from contributors outside the synergium. RESULTS: Recommendations of the Synergium are: Basic Science, Drug Development and Technology: There is a need to develop: (1) New systems of working together to break down the prevalent "silo" mentality; (2) New models of vertically integrated basic, clinical, and epidemiological disciplines; and (3) Efficient methods of identifying other relevant areas of science. Stroke Prevention: (1) Establish a global chronic disease prevention initiative with stroke as a major focus. (2) Recognize not only abrupt clinical stroke, but subtle subclinical stroke, the commonest type of cerebrovascular disease, leading to impairments of executive function. (3) Develop, implement and evaluate a population approach for stroke prevention. (4) Develop public health communication strategies using traditional and novel (eg, social media/marketing) techniques. Acute Stroke Management: Continue the establishment of stroke centers, stroke units, regional systems of emergency stroke care and telestroke networks. Brain Recovery and Rehabilitation: (1) Translate best neuroscience, including animal and human studies, into poststroke recovery research and clinical care. (2) Standardize poststroke rehabilitation based on best evidence. (3) Develop consensus on, then implementation of, standardized clinical and surrogate assessments. (4) Carry out rigorous clinical research to advance stroke recovery. Into the 21st Century: Web, Technology and Communications: (1) Work toward global unrestricted access to stroke-related information. (2) Build centralized electronic archives and registries. Foster Cooperation Among Stakeholders (large stroke organizations, nongovernmental organizations, governments, patient organizations and industry) to enhance stroke care. Educate and energize professionals, patients, the public and policy makers by using a "Brain Health" concept that enables promotion of preventive measures. CONCLUSIONS: To accelerate progress in stroke, we must reach beyond the current status scientifically, conceptually, and pragmatically. Advances can be made not only by doing, but ceasing to do. Significant savings in time, money, and effort could result from discontinuing practices driven by unsubstantiated opinion, unproven approaches, and financial gain. Systematic integration of knowledge into programs coupled with careful evaluation can speed the pace of progress.